Cobalt oxide nanoparticles: An effective growth promoter of Arabidopsis plants and nano-pesticide against bacterial leaf blight pathogen in rice - Ogunyemi, Solabomi Olaitan; Xu, Xinyan; Xu, Lihui; Abdallah, Yasmine; Rizwan, Muhammad; Lv, Luqiong; Ahmed, Temoor; Ali, Hayssam M.; Khan, Fahad; Yan, Chengqi; Chen, Jianping; Li, Bin (Ecotoxicology and environmental safety, 2023)
Recently, the application of cobalt oxide nanoparticles (Co3O4NPs) has gained popularity owing to its magnetic, catalytic, optical, antimicrobial, and biomedical properties. However, studies on its use as a crop protection agent and its effect on photosynthetic apparatus are yet to be reported. Here, Co3O4NPs were first green synthesized using Hibiscus rosa-sinensis flower extract and were characterized using UV–Vis spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction (XRD), transmission/scanning electron microscopy methods. Formation of the Co3O4NPs was attested based on surface plasmon resonance at 210 nm. XRD assay showed that the samples were crystalline having a mean size of 34.9 nm. The Co3O4NPs at 200 µg/ml inhibited the growth (OD600 = 1.28) and biofilm formation (OD570 = 1.37) of Xanthomonas oryzae pv. oryzae (Xoo) respectively, by 72.87% and 79.65%. Rice plants inoculated with Xoo had disease leaf area percentage (DLA %) of 57.25% which was significantly reduced to 11.09% on infected plants treated with 200 µg/ml Co3O4NPs. Also, plants treated with 200 µg/ml Co3O4NPs only had significant increment in shoot length, root length, fresh weight, and dry weight in comparison to plants treated with double distilled water. The application of 200 µg/ml Co3O4NPs on the Arabidopsis plant significantly increased the photochemical efficacy of PSII (ΦPSII) and photochemical quenching (qP) respectively, by 149.10% and 125.00% compared to the control while the non-photochemical energy dissipation (ΦNPQ) was significantly lowered in comparison to control. In summary, it can be inferred that Co3O4NPs can be a useful agent in the management of bacterial phytopathogen diseases. •Green synthesis of cobalt oxide (Co3O4) and characterization of obtained nanoparticles (NPs).•The Co3O4NPs exhibited significant antibacterial on growth and biofilm formation against Xanthomonas oryzae pv. oryzaes.•Co3O4NPs showed a high apoptosis and cellular membrane damage.•Co3O4NPs increased the agronomic parameters and biomass of rice plants.•Co3O4NPs improved the photosynthetic parameters of Arabidopsis, a model plant.